2020
DOI: 10.1021/jacs.0c05272
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Radiation Resistant Thorium–Binaphthol Metal–Organic Framework

Abstract: A thorium–organic framework (TOF-16) containing hexameric secondary building units connected by functionalized binaphthol linkers was synthesized, characterized, and irradiated to probe its radiation resistance. Radiation stability was examined using γ-rays and 5 MeV He2+ ions to simulate α particles. γ-irradiation of TOF-16 to an unprecedented 4 MGy dose resulted in no apparent bulk structural damage visible by X-ray diffraction. To further probe radiation stability, we conducted the first He2+ ion irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 32 publications
5
45
0
Order By: Relevance
“…Previous studies have thus shown a significant stability of MOF materials networks when irradiated under large doses of gamma rays. [7][8][9][10] Therefore, right after the events of Fukushima, the first studies about the capture of radionuclides in MOFs emerged in the literature. These species can be solubilized in water like actinides, technetium and cesium, [4,11] or gaseous noble gas like Xe, Kr [12] or iodine derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have thus shown a significant stability of MOF materials networks when irradiated under large doses of gamma rays. [7][8][9][10] Therefore, right after the events of Fukushima, the first studies about the capture of radionuclides in MOFs emerged in the literature. These species can be solubilized in water like actinides, technetium and cesium, [4,11] or gaseous noble gas like Xe, Kr [12] or iodine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MOFs can show a great chemical resistance, as they can be stable in liquid water, in high‐temperature steam or under irradiation. Previous studies have thus shown a significant stability of MOF materials networks when irradiated under large doses of gamma rays [7–10] . Therefore, right after the events of Fukushima, the first studies about the capture of radionuclides in MOFs emerged in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…9 ). Metal-organic frameworks (MOFs) featuring high radiation-resistance were known as exemplified by Th 6 O 4 (OH) 4 (H 2 O) 6 (C 22 O 6 H 12 ) 6 (TOF-16) (Supplementary Table 3 ) 43 . The investigation on radiation stability of cluster species has not been conducted and the only relevant case is an ultrastable [Hf 13 ] nanocluster, which is highly resistant to both concentrated acid and alkali 44 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) featuring high radioresistance were known and Th 6 O 4 (OH) 4 (H 2 O) 6 (C 22 O 6 H 12 ) 6 (TOF-16) represents the most radioresistant MOFs reported to date (Table S3). 43 The investigation on radiation stability of cluster species was conducted for the rst time in this work and the only relevant case is an ultrastable [Hf 13 ] nanocluster which is highly resistant to both concentrated acid and alkali. 44,45 Th-SINAP-100 represents the only reported radioresistant polynuclear cluster and one of the most radioresistant metal-organic materials in general.…”
Section: Radiolytic Stabilitymentioning
confidence: 99%